STRUCTURAL-GEOMETRIC INDICATORS OF THE LEFT VENTRICLE IN THE EVALUATION OF ELECTRICAL REMODELATION OF THE HEART OF THE HEAD OF CHRONIC SYSTEMIC INFLAMMATION IN THE INFLAMMATION - Nyshchuk-Oliynyk , N. B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2022)
Stable coronary artery disease in combination with type 2 diabetes mellitus remains one of the leading causes of disability and mortality. Therefore, the study of prognostic factors in the combination of these diseases remains relevant. The question of the influence of the inflammatory component on the development of atherosclerosis in patients with CCS in combination with type 2 diabetes mellitus is studied in this article. The influence of the severity of chronic systemic inflammation on the features of myocardial remodeling in such a combined pathology remains unclear. The aim of the study was to evaluate the features of LV myocardial remodeling on the background of chronic systemic inflammation in patients with stable coronary artery disease with concomitant type 2 diabetes mellitus. 120 patients were examined, including 90 patients with SCAD and type 2 diabetes mellitus (group I) and 30 patients with SCAD (group II). Patients in both groups had SCAD: angina class II-III by CCS classification. It was found that in patients with SCAD and type 2 diabetes mellitus and without it, type 1 diastolic heart dysfunction prevailed (relaxation disorders). Prognostically unfavorable type of remodeling, concentric LV hypertrophy, predominated in patients with SCAD associated with type 2 diabetes. The study showed that the increase in the integrated indicators of chronic systemic inflammation in patients with SCAD with concomitant type 2 diabetes mellitus associated with diastolic left ventricular dysfunction, hyperlipidemia, and this should be considered when choosing tactics of patient management. Conclusion: In our opinion, local disruption of lipid transport in the tissue is the basis of atherosclerotic lesions of the vascular wall, which develops independently of inflammation in it, but is significantly potentiated by the mediators of inflammation. Reconstruction of structural and functional parameters of the heart and disorders of intracardiac hemodynamics are characteristic of patients with SCAD without and in combination with type 2 diabetes mellitus, and in the latter case is more profound. These processes are initiated and deepened against the background of chronic systemic inflammation, which may be marked with elevated levels of ST2, hs-SRP, TMAO, TLR2, TLR4 and hematological indices.